The hidden face of Duchenne (Neuro)Muscular Dystrophy. Preliminary evidence of social cognition impairment as a feature of the neuropsychological phenotype of DMD - Parravicini, S.; Quaranta, C. A.; Dainesi, M. I.; Berardinelli, A. (Frontiers in Psychology, 2025)
AimTo study unexplored neuropsychological domains in the characterization of the Central Nervous System (CNS) involvement in Duchenne Muscular Dystrophy (DMD) that could be relevant based on the recent findings about dystrophin expression in human CNS.MethodA sample of DMD individuals (n = 20) underwent a neuropsychological battery encompassing standard cognitive assessments but also less explored social cognition skills. Wechsler scales and a developmental neuropsychological assessment (NEPSY-II) were adopted.ResultsOur sample performed significantly worse than the reference scores in the “social cognition” sub-items of the NEPSY-II; the difference persisted even when splitting the sample by Dp140 depletion or cognitive deficit. The difference in the “affect recognition” scores between the Dp140 + and the Dp140− subgroups was confirmed even after excluding the subjects with a cognitive deficit.InterpretationDystrophin is highly expressed in structures involved in the brain networks underlying some social cognition skills. Our results, which provide additional preliminary evidence of a possible specific impairment in this area, underscore the importance of considering social cognition as another feature of the CNS phenotype of DMD, consistent with a few other previous reports.